2010
DOI: 10.1007/s12033-010-9346-6
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference in Pigs: Comparison of RNAi Test Systems and Expression Vectors

Abstract: We have examined the use of RNA interference as a means of downregulating gene expression and provide the first comparison of shRNA and artificial miRNA constructs for transgenic livestock. Several in vitro assays were performed to identify the most effective RNAi constructs. shRNA and miRNA constructs achieved significant downregulation of two porcine target genes: the milk whey protein beta-lactoglobulin and the tumour suppressor p53. Results of different assays were, however, sometimes at variance, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Most of the 10 candidate miRNAs we tested in vitro were effective against ovine and bovine BLG, which recapitulates the successful design of effective RNAi molecules against porcine BLG in a previous study (14). Although a few of our miRNAs showed some target specificity for either of the two tested forms of BLG, this was not correlated with sequence homology between the miRNA and target.…”
Section: E8356 | Wwwpnasorgsupporting
confidence: 82%
See 3 more Smart Citations
“…Most of the 10 candidate miRNAs we tested in vitro were effective against ovine and bovine BLG, which recapitulates the successful design of effective RNAi molecules against porcine BLG in a previous study (14). Although a few of our miRNAs showed some target specificity for either of the two tested forms of BLG, this was not correlated with sequence homology between the miRNA and target.…”
Section: E8356 | Wwwpnasorgsupporting
confidence: 82%
“…A recent in vitro study demonstrated the effectiveness of several shRNAs and miRNAs directed against the porcine variant of BLG (14). We used artificial miRNAs based on the murine miRNA-155 to knock down BLG.…”
Section: E8356 | Wwwpnasorgmentioning
confidence: 99%
See 2 more Smart Citations
“…40 µg total protein was loaded in each lane and separated by 15% SDS-PAGE. Blotting and detection of porcine p53 and GAPDH was carried out as previously described [33]. Band densities were quantified using the image analysis tool ImageJ (http://rsb.info.nih.gov/ij/).…”
Section: Methodsmentioning
confidence: 99%